Thiophene‐S, S‐dioxidized Indophenine: A Quinoid‐Type Building Block with High Electron Affinity for Constructing n‐Type Polymer Semiconductors with Narrow Band Gaps. (2nd February 2016) - Deng, Yunfeng; Sun, Bin; He, Yinghui; Quinn, Jesse; Guo, Chang; Li, Yuning
Abstract: Three thiophene‐ S, S ‐dioxidized indophenine (IDTO) isomers, 3 a ( E, E, E ), 3 b ( Z, E, E ), and3 c ( Z, E, Z ), were synthesized by oxidation of an indophenine compound.3 b and3 c could be converted into the most‐stable3 a by heating at 110 °C. An IDTO‐containing conjugated polymer, PIDTOTT, was prepared using3 a as a comonomer through a Stille coupling reaction, and it possesses a narrow band gap and low energy levels. In organic field effect transistors (OFETs), PIDTOTT exhibited unipolar n‐type semiconductor characteristics with unexpectedly high electron mobility (up to 0.14 cm 2  V −1  s −1 ), despite its rather disordered chain packing.